The masquerading magician - Pandian, Gigi, 1975- (Pandian, Gigi, 1975- Accidental alchemist., 2016)
Zoe Faust works to decipher an ancient alchemy book before living gargoyle Dorian Robert-Houdin is trapped in stone forever, while a night out at a magic show ends in a murder with ties to crimes from Portland's past.